Affricates, Palatals and Iotization in Serbian: Representational Solutions to Longstanding Puzzles - Morén, Bruce (Poljarnyj vestnik, 2003)
This paper investigates the segment inventory of Serbian from both an articulatory and a phonological perspective, and it proposes a straightforward phonological analysis of both the inventory and the morpho-phonological process of iotization. The analysis is couched in terms of the Parallel Structures Model of feature geometry (Morén 2003a, b, c).